1977
DOI: 10.1002/cpt1977222196
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin in the treatment of diabetic symmetrical polyneuropathy

Abstract: The efficacy of phenytoin in the treatment of the symptoms of diabetic symmetrical polyneuropathy has been tested in a double-blind, crossover study. Symptoms were evaluated daily by linear analogue self-assessment, while control of blood glucose and plasma phenytoin level were monitored on a weekly basis. There was no significant improvement in symptoms on phenytoin, whether analyzed in aggregate, as pain alone, or on the last 3 days of each treatment week. Blood glucose, however, was elevated in diabetic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(60 citation statements)
references
References 4 publications
0
59
0
1
Order By: Relevance
“…112,113 A third study demonstrated the potential benefit of this medication when administered intravenously for the treatment of an acute exacerbation of various different types of neuropathic pain. These patients received a 15 mg/kg dose of phenytoin intravenously over a two-hour period.…”
Section: Phenytoinmentioning
confidence: 99%
“…112,113 A third study demonstrated the potential benefit of this medication when administered intravenously for the treatment of an acute exacerbation of various different types of neuropathic pain. These patients received a 15 mg/kg dose of phenytoin intravenously over a two-hour period.…”
Section: Phenytoinmentioning
confidence: 99%
“…Since that time, there have been few randomized, controlled trials of the analgesic effect of this drug in neuropathic pain. 4,5 The effect of phenytoin may be its membrane stabilizing effect, an effect it shares with lignocaine and mexiletine. With chronic, stable neuropathic pain, oral anticonvulsant drugs can be titrated to an effective dose.…”
Section: Discussionmentioning
confidence: 99%
“…5 The results of trials of phenytoin for the pain of diabetic neuropathy have been mixed. 6,7 Sodium valproate was not significantly better than placebo in patients with neuropathic pain due to spinal cord injury. 8 There is no high level evidence to support an effect for clonazepam on neuropathic pain.…”
Section: -3mentioning
confidence: 96%